2018
DOI: 10.3390/ijms19051480
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of Arachidonate 12/15-Lipoxygenase Improves α-Galactosidase Efficacy in iPSC-Derived Cardiomyocytes from Fabry Patients

Abstract: (1) Background: A high incidence of intervening sequence (IVS)4+919 G>A mutation with later-onset cardiac phenotype have been reported in a majority of Taiwan Fabry cohorts. Some evidence indicated that conventional biomarkers failed to predict the long-term progression and therapeutic outcome; (2) Methods: In this study, we constructed an induced pluripotent stem cell (iPSC)-based platform from Fabry cardiomyopathy (FC) patients carrying IVS4+919 G>A mutation to screen for potential targets that may help the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
13
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 56 publications
2
13
0
Order By: Relevance
“…After identification of pathological phenotypes in mutant iPSCs, candidate drugs can be tested for normalisation or minimisation of these phenotypic changes and the drug toxicity can be assessed [ 158 , 159 ]. Several molecules, such as interleukin-18 and arachidonate 12/15-lipoxygenase, have been demonstrated in Fabry iPSC-derived cardiomyocytes to be associated with disease progression, and respective inhibitors have been proposed to have an adjunctive effect with enzyme replacement therapy [ 123 , 160 ]. Future investigations could make use of an iPSC-based model to test the effectiveness of these inhibitors in the alleviation of Fabry phenotypes.…”
Section: Strategies For Using Ipsc-based Models For Disease Modelling and Drug Testingmentioning
confidence: 99%
“…After identification of pathological phenotypes in mutant iPSCs, candidate drugs can be tested for normalisation or minimisation of these phenotypic changes and the drug toxicity can be assessed [ 158 , 159 ]. Several molecules, such as interleukin-18 and arachidonate 12/15-lipoxygenase, have been demonstrated in Fabry iPSC-derived cardiomyocytes to be associated with disease progression, and respective inhibitors have been proposed to have an adjunctive effect with enzyme replacement therapy [ 123 , 160 ]. Future investigations could make use of an iPSC-based model to test the effectiveness of these inhibitors in the alleviation of Fabry phenotypes.…”
Section: Strategies For Using Ipsc-based Models For Disease Modelling and Drug Testingmentioning
confidence: 99%
“…There is evidence indicating that the vascular lesion formation in FD occurs as a result of endothelial cell dysfunction due to abundant Gb3 accumulation, which leads to altered cerebral perfusion and a pro-thrombotic phenotype [ 15 ]. In our previous works, we have generated FD patient-derived induced pluripotent stem cells (FD-iPSCs) and differentiated them into cardiomyocytes and endothelial cells [ 16 , 17 ]. FD-iPSC-derived cardiomyocytes exhibited remarkable cardiomyocyte hypertrophy, lysosomal abnormalities, Gb3 deposition (IL18, Alox12/15), and aberrant electrophysiology [ 16 ].…”
Section: Introductionmentioning
confidence: 99%
“…In our previous works, we have generated FD patient-derived induced pluripotent stem cells (FD-iPSCs) and differentiated them into cardiomyocytes and endothelial cells [ 16 , 17 ]. FD-iPSC-derived cardiomyocytes exhibited remarkable cardiomyocyte hypertrophy, lysosomal abnormalities, Gb3 deposition (IL18, Alox12/15), and aberrant electrophysiology [ 16 ]. FD-iPSC-derived endothelial cells also carry abnormal Gb3 accumulation and exhibit increased levels of reactive oxygen species and low expression of mitochondrial superoxide dismutase 2 [ 17 ].…”
Section: Introductionmentioning
confidence: 99%
“…Previously, we have generated FC patient-specific induced pluripotent stem cells (iPSCs) and differentiated them into iPSC-derived cardiomyocytes (iPSC-CMs) (Chou et al, 2017). Remarkably, these iPSC-CMs that carried GLA IVS4 + 919 G > A mutation, recapitulated FC-specific features such as Gb3 deposition and cardiomyocyte hypertrophy (Chien et al, 2016(Chien et al, , 2018. Thus, these patient-derived cells can be applied as an in vitro disease model for evaluating the efficacy of gene editing therapy.…”
Section: Introductionmentioning
confidence: 99%
“…In the present study, we generated patient-specific iPSC-CMs from a carrier of GLA IVS4 + 919 G > A mutation who was diagnosed with FC. These iPSC-CMs were characterized by disease-specific phenotypes and used as the disease model (Chien et al, 2016(Chien et al, , 2018. We demonstrated that the HDT-conjugated PU-PEI 600 -Mal could successfully increase the co-delivery of DNA template approach and CRISPR/Cas9 gene editing machinery leading to ameliorating FC-associated phenotypes.…”
Section: Introductionmentioning
confidence: 99%